PARTNERSHIP BETWEEN TEACHER AND SECONDARY SCHOOL STUDENT THROUGH LEARNING MATHEMATICS - Balode, Maija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
This article examines secondary school student and teachers cooperation through learning mathematics. The aim of the study is to find out whether the teacher and student cooperation is a partnership. The partnership is viewed as a cooperation where involved work toward mutual goals. Secondary school student - teacher partnership is possible if the teacher trusts students and together with them chooses the learning objectives, the teaching aids and methods of learning. Students take responsibility for their choices and they are motivated to accomplish them if there is possibility to make a choice. The article deals with teachers' views on teaching and students' opinions about what helps and what interferes learning mathematics.